Comparison of survival of adolescents and young adults with hematologic malignancies in Osaka, Japan. Issue 6 (2nd June 2016) - Nakata-Yamada, Kayo; Inoue, Masami; Ioka, Akiko; Ito, Yuri; Tabuchi, Takahiro; Miyashiro, Isao; Masaie, Hiroaki; Ishikawa, Jun; Hino, Masayuki; Tsukuma, Hideaki; ,
Abstract: The survival gap between adolescents and young adults (AYAs) with hematological malignancies persists in many countries. To determine to what extent it does in Japan, we investigated survival and treatment regimens in 211 Japanese AYAs (15–29 years) in the Osaka Cancer Registry diagnosed during 2001–2005 with hematological malignancies, and compared adolescents (15–19 years) with young adults (20–29 years). AYAs with acute lymphoblastic leukemia (ALL) had a poor 5-year survival (44%), particularly young adults (29% vs. 64% in adolescents, p = 0.01). Additional investigation for patients with ALL revealed that only 19% of young adults were treated with pediatric treatment regimens compared with 45% of adolescents ( p = 0.05). Our data indicate that we need to focus on young adults with ALL and to consider establishing appropriate cancer care system and guidelines for them in Japan.